Holiday Inn franchise : a study on the hotel accounting system / Nonya Kassim - Kassim, Nyonya (1992)
This project paper describes the theory and practise of franchising business format in hotel business. It considers the treatment of franchise fees and the major expenditure of hotel businesses. Throughout the discussion, I have tried to show some controls that is being emphasized on the expenditure, although it is not so detail. Discussion on expenditure is limited to the information provided which only covers the Food and Beverage (F&B) and Payroll, Taxes and Expenses Related (PTER). Authorisation and standard procedures determined by the hotel management are also considered as the elements of control. Therefore, the officer incharged must be responsible on reviewing and authorising the transactions.